A novel nearly plug‐flow membrane bioreactor for enhanced biological nutrient removal. Issue 1 (10th April 2012) - Meng, Fangang; Zhou, Zhongbo; Li, Lei; Li, Ruiyun; Jia, Xiaoshan; Li, Shiyu
Abstract : The feasibility of enhanced biological nutrient removal by a new process called nearly plug‐flow membrane bioreactor (NPFMBR) is studied. Results of long‐term observations showed that average removal degrees of (1) chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP) reached 95%, 85%, and 89%, respectively, at the steady operation period. Process success was further corroborated by batch experiments. Data of specific oxygen uptake rates demonstrated the abundance and/or high activities of ammonium oxidation bacteria and nitrite oxidation bacteria in the sludge. Observed specific rates of nitrification, denitrification, phosphorous release/uptake of the sludge were higher than those reported in previous research. Because of the unique flow pattern of sludge and alternant aerobic–anoxic operating conditions in the bioreactor, mass transfer and biotransformation of nutrients were expected to be improved. The NPFMBR could offer a new option for the wider application of MBRs. © 2012 American Institute of Chemical Engineers AIChE J, 59: 46–54, 2013